Application of GaBi software in identifying potential environmental impacts in fabrication of 3D bone tissue engineering - Senusi, Farasyafinaz; Mahmood, Salwa; Ngadiman, Nor Hasrul Akhmal; Mat Saman, Muhamad Zameri (2022)
– 3D printing technology has evolved over the years. There are many types of 3D printing methods introduced in this technology. As 3D technology continues to develop, medical industry technology follows the trend to ensure continuity in the medical and healthcare industry by being involved in the development of tissue engineering scaffold fabrication through 3D printing. One of the 3D printing methods is the fabrication of 3D bone tissue engineering scaffolds by 3D Digital Light Processing (DLP). Although 3D DLP methods in the fabrication of tissue engineering scaffolds help researchers develop new inventions, it might affect environmental sustainability. Therefore, the application of GaBi software will be applied in order to evaluate and identify the environmental impacts. Hence, this research paper will apply GaBi software as tool to analyse the fabrication of tissue engineering scaffolds in 3D DLP and determine the potential environmental impacts of this process. From the GaBi software analysis, this research will show the potential emissions that contribute to the environment that comes from 3D DLP operations. This research will contribute to 3D bone tissue engineering development to include environmental sustainability in each of the research and development involved in this technology.